The Karabakh problem in the mid-2010's - Krylov, Alexander (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
In this article a situation on the territory of Karabakh conflict and the positions of the conflicting parties are analyzed. These are based on a “package approach” (Armenia) and “step by step approach” (Azerbaijan).
Keywords: Modern History